SnS@C nanoparticles anchored on graphene oxide as high-performance anode materials for lithium-ion batteries - Mei, Jing; Han, Jinlu; Wu, Fujun; Pan, Qichang; Zheng, Fenghua; Jiang, Juantao; Huang, Youguo; Wang, Hongqiang; Liu, Kui; Li, Qingyu (Frontiers in Chemistry, 2023)
Tin (II) sulfide (SnS) has been regarded as an attractive anode material for lithium-ion batteries (LIBs) owing to its high theoretical capacity. However, SnS undergoes significant volume change during lithiation/delithiation, leading to rapid capacity degradation, which severely hinders its further practical application in LIBs. Here, we report a simple and effective method for the synthesis of SnS@C/G composites, where SnS@C nanoparticles are strongly coupled onto the graphene oxide nanosheets through dopamine-derived carbon species. In such a designed architecture, the SnS@C/G composites show various advantages including buffering the volume expansion of Sn, suppressing the coarsening of Sn, and dissolving Li2S during the cyclic lithiation/delithiation process by graphene oxide and N-doped carbon. As a result, the SnS@C/G composite exhibits outstanding rate performance as an anode material for LIBs with a capacity of up to 434 mAh g-1 at a current density of 5.0 A g-1 and excellent cycle stability with a capacity retention of 839 mAh g-1 at 1.0 A g-1 after 450 cycles.